Health Policy Analysis on the Containment of Antimicrobial Resistance (AMR) in India: A Mixed Methods Study of Antimicrobial Stewardship as a Pivotal Intervention in Tackling AMR - Singh, Chetan; Pandey, Anita; Singh, Lubhan (Anti-Infective Agents, 2024)
Objective: This policy report aimed at two goals, that is, to report the findings of the literature review and explore the perceptions of the key stakeholders in seeking better insight into the antimicrobial stewardship program (AMSP), and to develop antimicrobial resistance (AMR) policy recommendations for the Ministry of Health and Family Welfare (MoHFW), India, based on the findings from the rapid systematic review of the literature (both published and grey) and the views of key stakeholders. Methods: A mixed method approach using literature review and qualitative interviews has been applied. A rapid systematic literature review focusing on the antimicrobial stewardship program's key achievements and its implementation and impact, implementation challenges, gaps and barriers, and opportunities, has been carried out, which has been followed by conducting interviews of key stakeholders and reporting the findings along with the recommendations. Results: The findings have shown significant progress towards AMSP, such as expanding to 90 secondary-level hospitals and district-level hospitals/nursing homes, and the Indian Council of Medical Research antimicrobial resistance surveillance and research network (ICMR AMRSN) program. Education, training, and microbiological testing have been found to be the current focus areas. However, there exist challenges, including a lack of leadership support, diagnostic stewardship, and staffing of clinical pharmacists and infectious control nurses. Key gaps and barriers identified include setting up microbiology laboratories and hiring ICN nurses and clinical pharmacists. Opportunities have also been identified. Based on these findings, we have made succinct recommendations to address the themes and issues identified. Conclusion: Without new medicines, India will struggle to manage antimicrobial resistance. This situation calls for national oversight. This study has demonstrated AMSP as crucial for fighting this silent pandemic. The Indian government and policymakers must swiftly address critical challenges, gaps, and opportunities. These findings and recommendations might potentially strengthen the future antimicrobial resistance national action plan (AMR NAP).
Keywords: microbiology laboratories